2021
DOI: 10.7589/jwd-d-20-00032
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Herpesviruses in Passerine Birds Captured During Autumn Migration in Slovenia

Abstract: Herpesviruses (HVs) were detected by PCR in the cloacal swabs of 0.76% (4/525) clinically healthy free-living passerine birds from 32 different species captured in mist nets in Slovenia during the 2014 and 2017 autumn migrations. Herpesviruses were detected in the Eurasian Blackcap (Sylvia atricapilla), the Common Blackbird (Turdus merula), and the Eurasian Blue Tit (Cyanistes caeruleus). Phylogenetic analysis of partial DNA polymerase gene nucleotide sequences of the HV strains showed a distant relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…It seems that herpesviruses in raptors are more or less species-or order-specific, and that they differ from herpesviruses detected in pigeons, which provide opposite results from previous reports, in which the hypothesis was that identical herpesviruses are detected in raptor and pigeon populations (10,12,33). Furthermore, they differ from herpesviruses detected in songbirds, showing 49.7 to 76.1% nt identity to herpesviruses detected in songbirds in this and previous reports (14), which excludes the possibility of songbirds as the source of herpesvirus infection in birds of prey and owls. There appear to be only two published reports on the detection and partial characterization of herpesvirus in wild passerine birds.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…It seems that herpesviruses in raptors are more or less species-or order-specific, and that they differ from herpesviruses detected in pigeons, which provide opposite results from previous reports, in which the hypothesis was that identical herpesviruses are detected in raptor and pigeon populations (10,12,33). Furthermore, they differ from herpesviruses detected in songbirds, showing 49.7 to 76.1% nt identity to herpesviruses detected in songbirds in this and previous reports (14), which excludes the possibility of songbirds as the source of herpesvirus infection in birds of prey and owls. There appear to be only two published reports on the detection and partial characterization of herpesvirus in wild passerine birds.…”
Section: Discussioncontrasting
confidence: 68%
“…Generally, different studies have shown different levels of occurrence of herpesvirus in free-living bird species. In owls, herpesvirus was detected at levels from 9.41% (16/170) (15) to 14.5% (8/55) (13), and in seabirds from 3.8% (4/104) (31) to 5.6% (14/250) (32), whereas a lower presence of herpesvirus was detected in passerine birds, at only 0.8% of positive samples (4/525) (14). In studies that examined free-living birds from different orders, the highest occurrence of herpesvirus (20.4%; 18/88) was seen in a study from Poland, where the presence of herpesvirus was detected in domestic pigeons, birds of prey, and non-raptorial birds (12).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In owls, the male commonly offers food to the female during the courtship ritual and, furthermore, the male and female both feed their offspring during the reproduction period [27]. The results showed that oropharyngeal swabs are more suitable for detection of herpesvirus in owls; however, although herpesvirus was not detected in cloacal swabs, which could also be due to the presence of inhibitors in the swabs, the importance of cloacal swabs in the detection of herpesvirus should not be neglected, as previous reports have shown [23,40]. Our study was conducted during peak prey years [41], and thus with low nutritional stress for owls, but even here transmissions within the nests were detected.…”
Section: Discussionmentioning
confidence: 99%